Auxiliary diagnostic value of D2-40 in early lung adenocarcinoma and precursor lesions. Issue 9 (30th June 2021) - Hongxia, Wang; Qingqing, Yi; Chunfang, Zhang; Jun, Chen; Jing, Li; Guofeng, Lu; Rong, Yang
Abstract : Aims: Objective to investigate whether D2-40 can be used as a marker of early lung adenocarcinoma and precursor lesions. Methods: In order to explore the value of D2-40, a monoclonal antibody that recognises the podoplanin, as an auxiliary diagnostic marker to aid the diagnosis of these conditions, we performed the immunohistochemical (IHC) staining using early lung adenocarcinoma, infiltrating adenocarcinoma, benign lung lesions and relevant peritumour normal tissues. The microscopic examination was performed to analyse the D2-40 IHC staining. Results: We found that there was no D2-40 staining in 47 cases of early stage lung adenocarcinoma and precursor lesions; only 1 of the 32 cases (3.13%) of infiltrating adenocarcinoma stained positive. There was 100% D2-40 staining in 30 cases of benign lung lesions and 79 cases of peritumour normal tissues. The positivity rate in carcinoma group was 1.27% and the normal tissue group was 100%, (p<0.01). Based on our findings, we concluded that D2-40 IHC staining in lung adenocarcinoma and precursor lesions compared with normal alveolar epithelia displayed the 'none or all' phenomenon. Conclusions: The results from our study suggested that D2-40 can be sued as auxiliary diagnostic tool in early lung adenocarcinoma and its precursor lesions.